Beneficial effects of training at the anaerobic threshold in addition to pharmacotherapy on weight loss, body composition, and exercise performance in women with obesity - Ozcelik, Oguz; Ozkan, Yusuf; Algul, Sermin; Colak, Ramis (Dove Medical Press Ltd, 2015)
Objective: The aim of this study was to determine and compare the effects of weight loss achieved through orlistat therapy alone or a combination of orlistat and an aerobic exercise training program on aerobic fitness and body composition in obese females. Methods: Twenty-eight obese patients were randomly assigned to receive 12-week treatment with hypocaloric diet-orlistat or diet-orlistat-exercise. Each participant performed an incremental ramp exercise test every 4 weeks to measure aerobic fitness. Fourteen participants performed continuous exercise (approximately 45 minutes per session) at a work rate corresponding to the anaerobic threshold three times per week. Results: A decrease in the fat mass to body weight ratio of 3.8% (P=0.006) was observed at the end of the 12 weeks in the orlistat group, while a decrease of 9.5% (P=0.001) was seen in the orlistat-exercise group. Maximal exercise capacity increased by 46.5% in the orlistat-exercise group and by 19.5% in the orlistat group. Conclusion: While orlistat therapy resulted in an improvement in body composition and aerobic fitness at the end of the 12-week period, its combination with exercise training provided improvements in the same parameters within the first 4 weeks of the study. These additional beneficial effects of combining aerobic exercise with orlistat therapy are important with regards to obesity-associated risk factors.
Keywords: obesity; orlistat; body mass index; anaerobic threshold; aerobic fitness